Product market competition, R&D investment, and stock returns - Gu, Lifeng (Journal of Financial Economics, 2016)
A standard real options model predicts a strong positive interaction effect between research and development (R&D) investment and product market competition. R&D-intensive firms tend to be riskier and earn higher expected returns than R&D-weak firms, particularly in competitive industries. Also, firms in competitive industries earn higher expected returns than firms in concentrated industries, especially among R&D-intensive firms. Intuitively, R&D projects are more likely to fail in the presence of more competition because rival firms could win the innovation race. Empirical evidence largely supports the model׳s predictions.